Piacenzian Environmental Change and the Onset of Cool and Dry Conditions in Tropical South America. Issue 11 (30th October 2020) - Grimmer, Friederike; Dupont, Lydie M.; Jung, Gerlinde; Wefer, Gerold
Abstract: The Piacenzian (3.60–2.58 Ma) covers the last stage of the Neogene just before the Earth's climate turned from relatively stable warm conditions to the cooler climate with high amplitude glacial‐interglacial oscillations of the Pleistocene. Even during this period early fluctuations towards cooler conditions occurred, and sea surface temperature (SST) reconstructions show stepwise increasing gradients. The zonal Pacific SST gradient which indicates the strength of the Walker circulation appears to have increased in two steps starting in the Piacenzian. We investigated vegetation and climate change in western equatorial South America under the influence of the Walker circulation and to detect signs for the onset of cooling in the tropics. We studied vegetation changes in western Ecuador using palynological analysis of 88 sediment samples from marine Ocean Drilling Program Site 1239 dated between 3.9 and 2.7 Ma. A general trend towards more open vegetation is observed. The climate changes towards cooler conditions, which is manifested by a lowering of the forest line from 3.3 Ma on. The increase of Amaranthaceae pollen after 3.1 Ma suggests drier conditions along the coast. A comparison with mid‐Piacenzian warm period (mPWP) modeling shows that data and models agree regarding a drier coastal climate during the mPWP. The isochronous occurrence of environmental changes in the presented record, that is, cooling and coastal drying, with the first major pulse of ice‐rafted debris and cooling temperatures in the Northern Hemisphere (between 3.28 and 3.31 Ma) suggests that these changes might have been a precursor of the intensification of the Northern Hemisphere glaciation. Plain Language Summary: Around 3.6 to 2.6 million years ago was a time in Earth's history when many conditions were similar to today like the arrangement of the continents, vegetation, and greenhouse gas concentrations. However, the Arctic was not yet covered by ice sheets, and the global climate was warmer, making this time period well suited to study the drivers and mechanisms of warm climates. Towards the end of this period, global climate started to cool, which is known mainly from Northern Hemisphere climate reconstructions. We wanted to find out if cooling and drying conditions found in other records also occurred in the South American tropics. Fossil pollen assemblages preserved in marine sediments can tell us which plants grew in our study area (broadly western Ecuador). Since plants have different (known) climatic requirements, we can reconstruct past rainfall and temperatures as well. We find cooling and drying of neotropical climate, possibly linked to the period preceding the intensification of the Northern Hemisphere glaciations. Studying past climates can help us to better understand and constrain present and future climate developments. Key Points: We present a marine pollen record of climate and vegetation change in western equatorial South America during the Piacenzian From around 3.3 Ma, the vegetation became more open, the climate became cooler and the coastal area became drier The inferences from the pollen record are in agreement with climate modeling results for the mid‐Piacenzian warm period